Analysis of digital tourism development strategies as promotion of water blow tourism Nusa Dua Bali - I Made Suardika; I Wayan Eka Mahendra; I Made Darsana (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The tourism sector has a large contribution in increasing state and regional income. Therefore, it is important to make efforts to develop tourism in Indonesia. Water Blow Nusa Dua is one of the tourist destinations on the island of Bali which has a unique attraction and can be visited by tourists. One effort that can be made to increase the number of visits is through digital tourism by utilizing technology as a promotional medium. This research aims to find out government policies, strategies and decisions in developing internet-based tourism (digital tourism) using tourism website data, internet reviews about tourism, and social networks related to the Water Blow Nusa Dua Bali tourism. The qualitative method used in the research is an internal factor evaluation (IFE) and external factor evaluation (EFE) matrix with SWOT analysis by reviewing internal factors (strengths and weaknesses) and external factors (opportunities and threats) which are taken into consideration in developing digital tourism in Water Blow Nusa Dua. The results of this research found that tourism promotion through digital tourism using the internet is still not optimally carried out by the Badung Regency government so it is necessary to increase promotion through social media. This research can be used as recommendation material for the government or related parties in determining the direction of digital tourism development